2007
DOI: 10.1016/j.urology.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Assay Standardization Bias: Different Prostate Cancer Detection Rates and Clinical Outcomes Resulting from Different Assays for Free and Total Prostate-Specific Antigen

Abstract: OBJECTIVESNumerous commercial assays are available for measuring total and free prostate-specific antigen (PSA) levels in serum. These assays can be referenced to different laboratory standards, and interassay variability occurs. Patients and physicians might be affected by the variability between PSA assays that results from the use of different PSA standards. METHODSWe prospectively compared the free and total PSA measurements obtained using two commercially available PSA assays in 103 participants from a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…20 Although measurement of PSA is subject to some variability by assay 21 and day-to-day variation, 22 and assignment of Gleason score is marked by a degree of interobserver variation among pathologists, 23 these measurements are likely more reproducible than determination of clinical stage and, thus, serve as more objective markers of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although measurement of PSA is subject to some variability by assay 21 and day-to-day variation, 22 and assignment of Gleason score is marked by a degree of interobserver variation among pathologists, 23 these measurements are likely more reproducible than determination of clinical stage and, thus, serve as more objective markers of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Kort et al recently concluded that the results of other assays also deviate from expected tPSA values if the WHO 96/670 reference preparation is applied (regression slopes between 0.99 and 1.08), showing that further efforts are needed to improve the interchangeability of tPSA assays (17,18,21 ). In addition, we emphasize that although use of a biopsy cutoff of 3.0 or 4.0 g/L is com- (4,13,29,30 ). This study and others, however, evaluated the effects of different tPSA assays, which have different performance characteristics.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, comparability of the values depends strongly on whether the assay was standardized to the WHO calibrator or to the older Hybritech calibrator, which yield values differing by about 20% [3••,28•,29,30]. For these reasons, caution is required when comparing results from different commercial tPSA assays and from the same commercial assay standardized to different calibrators [2•,28•,29,30]. Different assays and different calibrators may explain some differences in reported PCa detection rates and clinical outcomes [28•,2932].…”
Section: Challenges Of Prostate-specific Antigen Detectionmentioning
confidence: 99%
“…For these reasons, caution is required when comparing results from different commercial tPSA assays and from the same commercial assay standardized to different calibrators [2•,28•,29,30]. Different assays and different calibrators may explain some differences in reported PCa detection rates and clinical outcomes [28•,2932]. …”
Section: Challenges Of Prostate-specific Antigen Detectionmentioning
confidence: 99%